REVIEW OF IMAGE ENCRYPTION AND DECRYPTION TECHNIQUES FOR 2D IMAGES - Shah, Jalpa; Dhobi, JS (International Journal of Engineering Technologies and Management Research, 2018)
In the emerging era of Internet, multimedia software and application security of images is of major concern. To offer security to these images encryption is the way for robust security. With Image Encryption it becomes difficult to analyze the image that is communicated over untrusted network. Also it provides security for any unauthorized access. The paper provides an introduction to cryptography and various image encryption techniques are reviewed for 2D images.